Developing approaches to treating arterial hypertension in regard to possible pathways of angiotensin II synthesis - N. M. Chikhladze (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study antihypertensive effects of AT1-receptor blocker eprosartan and ACE inhibitor enalapril, in regard to leading pathway of angiotensin II (AT II) synthesis among arterial hypertension (AH) patients with various functional status of renin-angiotensin-aldosterone system (RAAS). Material and methods. In total, 54 AH patients were examined. RAAS parameters and chymase activity were measured at rest and after orthostatic and captopril tests. Thirty-eight out of 54 patients were included into an open comparative cross-over two-group study, being administered eprosartan or enalapril. Antihypertensive effect was assessed after 8 weeks of treatment, by office blood pressure (BP) levels and 24-hour BP monitoring (BMP) results. Results. Basic criteria for identifying leading AT II synthesis pathway were proposed: antihypertensive reaction type in captopril test and baseline level of plasma chymase activity. Assessing eprosartan and enalapril treatment efficacy, it turned out that both agents had significant, similar antihypertensive effects, with eprosartan’s dominating influence on pulse BP. Eprosartan therapy was more effective in low-renin AH patients. Enalapril was less effective than eprosartan in patients with alternative, chymase-dependent pathway of AT II synthesis. Conclusion. Leading pathways of AT II synthesis in AH patients might be BP reduction in captopril test and baseline level of plasma chymase activity. Eprosartan therapy was more effective in low-renin and severe AH, that might be linked to its effects on alternative pathway of AT II synthesis.